Dealing with well-formed and malformed packets, associated with point of failure that cause network security breach - Al Naeem, Mohammed Abdul Aziz; Abubakar, Adamu; Hafizur Rahman, M. M. (IEEE, 2020)
T It is quite challenging to understand the weakest single points of failure in a network because it is the point where an entire network system can be taken down. The paths leading to a point of failure, and the status of packets that causes network security breaches were examined by Intent-Based Networking approach in this study. Two algorithms are proposed, utilizing single-path and multipath in transmission flow. Every path is potentially weak and a point of failure for which a network security can be breached. Two sets of rules, namely, ‘‘vulnerability rules policies’’ with ‘‘rules formulation’’ from the regions of connection recognized by Euler’s theorem were outlined. The intent is to use these sets of rules in finding the point of failure the packet status that is leading to possible security breaches within network connections. The frequencies of the packets that are liable to create security breaches and the paths where they originate are analyzed. Well-formed packet originating from the least likely weak point of failure is associated the network security breach than malformed packets. This study has contributed to revealing that network security breaches are influenced by the paths with least likely point of failure from well-formed packets.